C** Programmers' Guide - Trinity College (Dublin, Ireland). Distributed Systems Group (Trinity College Dublin, Department of Computer Science, 1992)
The C** extensions to C++ for distributed and persistent programming in C++ are described.
Keywords: Computer Science